Soil Moisture Monitoring System in Arugula Plants (Eruca Sativa) Using Microcontroller Esp8266 NodeMCU - Perangin-angin , Bisman; Simanjuntak, Hartono (Journal of Technomaterial Physics, 2021)
The Internet of Things (IoT) is getting great attention from researchers nowadays, as it becomes an important technology that promises intelligent human life, with between objects, machines and everything together with people. IoT represents a system consisting of real-world things, and sensors attached to or combined with these things, connected to the internet through cable and wireless network structures. With IoT, the world will be smart in every aspect because IoT will provide smart city facilities, smart health care, smart homes and buildings, in addition to many important applications such as smart energy, grid, transportation, waste management and monitoring. One microcontroller device that supports the use of IoT is the Esp8266 NodeMCU integrated with the Blynk application. So that with the design of a system to control/monitor the condition or moisture of the soil in arugula plants, the cultivation or production can be more maximal and efficient.